Do seductive details do their damage in the context of graph comprehension? Insights from eye movements. Issue 1 (11th December 2018) - Strobel, Benjamin; Grund, Simon; Lindner, Marlit Annalena
Summary: In educational research, interesting but irrelevant materials are often considered seductive details, which are suspected to have detrimental effects on learning. Although seductive details have been mostly examined in the context of text comprehension, such elements are also used in graphs (e.g., depicting data points). In the present experiment, we investigated both seductive text and seductive pictures in the context of graph comprehension as well as the interaction of seductive details with spatial working memory capacity (SWMC). We recorded N = 68 students' eye movements, while they analyzed bar graphs in a within‐subject design. Data were analyzed with linear mixed‐effects models. Results show that seductive details did not affect students' graph reading performance but prolonged the task processing time. Eye‐fixation measures revealed that additional processing time was best explained by attention distraction towards the seductive material. SWMC did not affect the presence or the extent of the seductive details effect.